2020
DOI: 10.3390/insects11020118
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of the Diamondback Moth (Plutella xylostella) in the UK and Provision of Decision Support for Brassica Growers

Abstract: In the UK, severe infestations by Plutella xylostella occur sporadically and are due mainly to the immigration of moths. The aim of this study was to develop a more detailed understanding of the phenology of P. xylostella in the UK and investigate methods of monitoring moth activity, with the aim of providing warnings to growers. Plutella xylostella was monitored using pheromone traps, by counting immature stages on plants, and by accessing citizen science data (records of sightings of moths) from websites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The geographical destination and source area of the migrating moths were estimated via constructed trajectories carried out by the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) facility ( Stein et al 2015 , Rolph et al 2017 ). HYSPLIT is a professional model for computing simple air parcel trajectories that has previously been employed to simulate insect migratory trajectories (e.g., Westbrook et al 2019 , Wainwright et al 2020 ) and specifically to investigate likely source and destination regions ( Rosenberg and Magor 1983 , Dingle 1996 , Chapman et al 2010 , Zhang et al 2018 ). The trajectory simulations were based on the following assumptions: (1) the moths flew approximately downwind ( Chen et al 1989 ); (2) they remained at the altitude of the 925 hPa level; (3) wind speed was assumed to be the moths’ flight speed, flights lasted 8 hr (from 19:00 to 03:00, Beijing local time), and; (4) flights continued for up to five successive nights.…”
Section: Methodsmentioning
confidence: 99%
“…The geographical destination and source area of the migrating moths were estimated via constructed trajectories carried out by the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) facility ( Stein et al 2015 , Rolph et al 2017 ). HYSPLIT is a professional model for computing simple air parcel trajectories that has previously been employed to simulate insect migratory trajectories (e.g., Westbrook et al 2019 , Wainwright et al 2020 ) and specifically to investigate likely source and destination regions ( Rosenberg and Magor 1983 , Dingle 1996 , Chapman et al 2010 , Zhang et al 2018 ). The trajectory simulations were based on the following assumptions: (1) the moths flew approximately downwind ( Chen et al 1989 ); (2) they remained at the altitude of the 925 hPa level; (3) wind speed was assumed to be the moths’ flight speed, flights lasted 8 hr (from 19:00 to 03:00, Beijing local time), and; (4) flights continued for up to five successive nights.…”
Section: Methodsmentioning
confidence: 99%
“…xylostella are oligophagous insects that use closely related host plants for oviposition and feeding. Thelarvae feed on Brassicaceae crops including cabbage, broccoli, cauliflower, and canola (Wainwright et al, 2020;Miluch et al, 2013 Glucosinolates, a class of protective chemicals, do not defend against DBM attack, but serve as effective feeding and oviposition stimulants. Furlong et al, (2008) reported that the enzyme glucosinolate sulfatase in the gut of DBM break glucocinolates and the DBM is not affected by the level of brassica glucosinolate.…”
Section: Host Plant Interactionmentioning
confidence: 99%
“…Although most DBM adults remain on their natal host plants in their whole lives, some DBM adults move greater distances (Furlong et al ., 2013). For example, annually DBM adults migrate from continental Europe to the United Kingdom, where they cannot survive the harsh winter conditions (Wainwright et al ., 2020). Furthermore, gene flow assessment indicates that migrations of DBM are often directed northward in spring and summer and southward in autumn in China (Wei et al ., 2013; Li et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic female sex pheromone has been used as a mating disruption agent to reduce population densities of the diamondback moth (Nemoto et al ., 1992). Sex pheromone traps are also used for monitoring field populations of this moth (Iga, 1985; Kuwahara et al ., 1995; Dai et al ., 2008; Wainwright et al ., 2020), but information from trapping is limited to the number of males caught. To better understand the ecology and physiology of the wild adult males, an estimation of male age is required.…”
Section: Introductionmentioning
confidence: 99%